The Effect of Ni-ZSM-5 Catalysts on Catalytic Pyrolysis and Hydro-Pyrolysis of Biomass - Ding, Ya-Long; Wang, Hua-Qin; Xiang, Mei; Yu, Pei; Li, Rong-Qiang; Ke, Qing-Ping (Frontiers in Chemistry, 2020)
With the demand of energy and re-utilization of wastes, the renewable lignocellulosic biomass, has attracted increasing and significant attention for alleviating the growing energy crisis and environment problems. As main components of lignocellulosic biomass, lignin, cellulose and hemicellulose are connected by hydrogen bond to form a compact skeleton structure, resulting the trenchant condition of biomass pyrolysis. Also, pyrolysis products of above three main constituents contain a large amount of oxygenates that cause low heating value, high corrosiveness, high viscosity and instability. Meanwhile, zeolites are of considerable significance to the conversion of lignocellulosic biomass to desirable chemical products on account of fine shape selectivity and moderate acid sites and strength. Among numerous zeolites, ZSM-5 based catalysts have been most extensively studied, and the acidity and porosity of ZSM-5 can be tuned by changing the content of Si or Al in zeolite. Beyond that, doping of other metal elements, such as Mn, Co, Ni, Ga, Ce, Pt, into ZSM-5 is also an efficient way to regulate the strength and density of acid sites in zeolite precisely. This review focused on the recent investigation of Ni-modified microporous ZSM-5 used in catalytic pyrolysis of lignin and cellulose. The application of metal-modified hierarchical ZSM-5 is also covered.